MUKORMIKOSIS - Adawiyah, Robiatul (JKK (Jurnal Kedokteran Klinik), 2017)
ABSTRACT: Mucormicosis is a mold which is currently beginning to be widely found in immunocompromised persons. Clinical manifestations are often influenced by the underlying diseases. This condition determine the type of sample taken for diagnosis. Enforcement of diagnosis is very important in the management that ultimately determines the outcome of the patient.Keywords: Mold, immunocompromised, mucormycosisÂ ABSTRAK:Â  Mukormikosis adalah jamur kapang yang saat ini mulai banyak ditemukan pada individu imunokompromis. Manifestasi klinis sering dipengaruhi oleh penyait yang mendasarinya. Hal itu mempengaruhi jenis sampel yang diambil guna penegakan diagnosis. Penegakan diagnosis sangat penting dalam tatalaksana yang akhirnya menentukan outcome pasien.Kata Kunci: Jamur filamen, imunokompromis, mukormikosis